Penerapan Sistem Etle terhadap Pelanggaran Kendaraan Bermotor dalam Berlalu Lintas - Sabiyan Yudhistira Hekmatiar; Wiwin Yulianingsih (UNES Law Review, 2023)
ETLE (Electronic Traffic Law Enforcement) is basically the result of technological developments that keep moving forward, which are then used in the framework of less traffic control. This is the same as digitizing law enforcement against traffic violations. With the existence of ETLE, of course the hope is that it can run effectively in order to create order in traffic for motorized vehicles. Based on this, it is worth exploring the implementation of ETLE implementation as well as the obstacles, to be linked to the effectiveness of the law. This research is an empirical juridical research, with a qualitative approach. The field study was conducted at Polretabes Surabaya. Sources of data are primary and secondary data, in which there are primary, secondary and tertiary legal materials. Collecting data using the method of observation, interviews, and literature study. Data analysis used descriptive analytical method. The results of the study show that the implementation of ETLE as mandated by the Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation begins with planning and ending with implementation. However, ETLE with CCTV cannot be implemented in the Surabaya area. In its implementation, discrepancies are still found that are contrary to the objectives and benefits of implementing ETLE. In addition, there are still obstacles in its implementation, which shows that the implementation of ETLE is still not effective.